Інноваційні підходи до загоєння обширних ранових дефектів стоп у хірургії пізніх ускладнень у хворих із синдромом діабетичної стопи - Свиридов, М. В. (Clinical Endocrinology and Endocrine Surgery, 2008)
The analysis of surgical treatment of 112 patients with the purulent-necrotic forms of diabetic foot syndrome in complex treatment which one has applied an skin equivalent with autofibroblasts, was carried out. 40 patients have compounded controls, which one we treated by traditional ways. The use of cellular-tissue therapy in a healing of trophic ulcers and of a wound defect has allowed to execute early autodermoplasty from 90% of healing of an skin autotransplantat for 96 patients of a basic group and to achieve 96,4% of healing of a wound defect during 25 days. The healing of wounds for patients of control group lasted during 2-3 months.